2022
DOI: 10.31219/osf.io/bf286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fostering Research Integrity through the promotion of fairness, equity and diversity in research collaborations and contexts: Towards a Cape Town Statement (pre-conference discussion paper)

Abstract: The World Conferences on Research Integrity have produced significant collaborative conference statements including the Singapore Statement on Research Integrity and more recently the Hong Principles on Researcher Assessment. The 7th World Conference on Research Integrity (7WCRI) takes place in Cape Town from the 29th May 2022 to 1st June 2022. The theme of the conference is Fostering Research in an unequal world. We have proposed the Cape Town statement on Fostering Research Integrity through the promotion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Interviewees expressed concern about inequity in sharing the benefits of collaborative genomic research and biobanking. Similar concerns have been raised by several scholars (Horn et al, 2022; Munung & de Vries, 2020; Mwaka et al, 2022; Rosenbloom et al, 2017; Yakubu et al, 2018). This has partly been attributed to the inequalities and power imbalances between collaborating partners and lack of appropriate ethical and legal frameworks (de Vries et al, 2017; Mwaka et al, 2022; Yakubu et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Interviewees expressed concern about inequity in sharing the benefits of collaborative genomic research and biobanking. Similar concerns have been raised by several scholars (Horn et al, 2022; Munung & de Vries, 2020; Mwaka et al, 2022; Rosenbloom et al, 2017; Yakubu et al, 2018). This has partly been attributed to the inequalities and power imbalances between collaborating partners and lack of appropriate ethical and legal frameworks (de Vries et al, 2017; Mwaka et al, 2022; Yakubu et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Collective course faculty selection, collaborative lecture delivery, joint selection of student groupings, and respect for institutional policies were a few ways that equity was pursued in the partnership. Available resources to help guide equity in international academic collaborations include the Fair Trade Learning Rubric, the Equity Tool for Valuing Global Health Partnerships [ 13 , 51 ], the research fairness initiative tool, and the THET principles in partnership for Global Health framework among others [ 52 , 53 ]. Evaluation of the course using the Fair Trade Learning rubric showed that mutuality of course leadership was ensured, and reasons for the partnership were understood and welcomed by diverse stakeholders, resulting in ideal institutional and learner theories of change.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil collaborates with institutions of higher and lower research capacity compared to its own institutions (Research in Brazil, 2018 ). Nevertheless, the cooperation among scientific institutions with unequal resources should consider balancing potentialities and fragilities to build trust and increase a research integrity culture (Schroeder et al, 2019 ; Horn et al, 2022 ).…”
Section: Current Challenges and Future Stepsmentioning
confidence: 99%